Presence of Intratumoral Stem Cells in Breast Cancer Patients with or without BRCA Germline Mutations - F. Singer, C.; Zabkova, P.; Rappaport, C.; Muhr, D.; Pfeiler, G.; Gschwantler-Kaulich, D.; Fink-Retter, A.; Staudigl, C.; Walter, I.; Hudelist, G.; Spiess, A.-C.; Kubista, E. (Current Cancer Drug Targets, 2012)
Background: BRCA-1/2 germline mutations are responsible for early onset breast cancer and familial association. The underlying causes of the characteristic phenotypic behavior are not completely understood, but mammary stem cells appear to have a key role in this process. Materials and Methods: We have investigated the presence of mammary stem / progenitor cells in normal tissues and in tumor tissues obtained from women with and without BRCA1/2 germline mutations by utilizing ALDH-1 immunohistochemistry. Results: Isolated ALDH-1 positive cells were found in 15/28 (54%) of breast cancer samples from women with BRCA 1 or 2 mutations and in 33 /51 (65%) of matched sporadic breast cancer cases (p=0.5949, Chi Square test). While mammary stem cells were also detected in non-malignant breast lesions, only 41% of the tissues contained ALDH-1 positive cells (p=0.0371, Chi Square test). In patients with BRCA germline mutations ALDH-1 positive cells were more common in p53 positive (p=0.0028, Chi Square test) tumors, in high grade (p=0.0796), and in larger tumors (p=0.0604), while no such association was seen in sporadic cancer cases. In our patients, the expression of ALDH-1 positive cells in breast cancer was neither associated with disease-free and overall survival, nor time to metastasis. Conclusion: Breast cancers from BRCA mutation carriers do not harbor more ALHD-1 positive cells than sporadic tumors, and their more aggressive phenotype can thus not be explained by an increased stem cell pool. The presence of ALDH-1 in normal breast tissue suggests that additional factors determine the biological behavior of mammary stem cells.
Keywords: Progression-Free Survival